2002
DOI: 10.1097/00005537-200205000-00026
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Tonsillectomy and Adenoidectomy on Serum IGF‐I and IGFBP3 Levels in Children

Abstract: These findings revealed that obstructive adenoid and tonsillar hypertrophy may cause decreased serum IGF-I levels by affecting the GH-IGF-I axis, and T&A is an effective therapeutic measure in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
10

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 19 publications
3
33
0
10
Order By: Relevance
“…Two other studies also found higher IGF1 and IG-FBP3 values post T&A. 39,40 In our study, besides IGF1, GH values were also determined in 18 subjects, under basal conditions. Contrary to expectations, the basal GH values tended to be higher pre-op although not statistically significant.…”
Section: Discussionsupporting
confidence: 75%
“…Two other studies also found higher IGF1 and IG-FBP3 values post T&A. 39,40 In our study, besides IGF1, GH values were also determined in 18 subjects, under basal conditions. Contrary to expectations, the basal GH values tended to be higher pre-op although not statistically significant.…”
Section: Discussionsupporting
confidence: 75%
“…[1][2][3][4][5] Adenotonsillar hypertrophy is the primary cause of OSAS in children, and is usually treated with adenotonsillectomy (AT). AT has been reported to accelerate weight [6][7][8][9][10][11][12][13][14] in children with baseline failure to thrive (FTT), 1,3,4,15 normal weight patients, 9,11,14,[16][17][18][19][20] obese individuals, 9,13,16,21,22 and infants. 10 The majority of studies also have demonstrated an increase in the height growth rate after AT for OSAS, 3,6,11,17,23,24 but other studies reported no significant differences.…”
Section: (Continued On Last Page)mentioning
confidence: 99%
“…Pudemos observar em outra série que há uma melhora significativa da mastigação e deglutição 7 que podem facilitar a ingesta alimentar, entretanto outros autores observaram que a ingesta calórica antes e após a adenoamigdalectomia é semelhante 15 . Cita-se ainda a relação com a baixa saturação sangüínea noturna de oxigênio, acidose noturna e aumento do gasto energético resultado do aumento do trabalho respiratório 16 . Estudos recentes mostram que 34 a 61% das crianças com hipertrofia adenoamigdaliana que são submetidas a cirurgia apresentam graus variáveis de hipoxemia e distúrbios do sono que não são normais 8 .…”
Section: Discussionunclassified
“…A apnéia do sono, por provocar despertares freqüentes, está associada a uma liberação irregular da secreção do hormônio de crescimento (GH), interferindo no crescimento. 8 Observa-se após a adenoamigdalectomia um aumento da secreção do GH 8,16 assim como de IGF-I (Insulin-like Growth Factor -fator de crescimento semelhante à insulina) e IGFBP3 (Fator de crescimento semelhante à insulina ligado à proteína transportadora B3). Este fator é responsável pelo efeito anabólico do GH 16 .…”
Section: Discussionunclassified